2010
DOI: 10.1503/cmaj.091711
|View full text |Cite
|
Sign up to set email alerts
|

The impact of herpes zoster and postherpetic neuralgia on health-related quality of life: a prospective study

Abstract: H erpes zoster, which is characterized by dermatomal pain and vesicular rash, 1,2 results from reactivation of the varicella-zoster virus. 3,4 The average lifetime risk of herpes zoster in developed countries is estimated to be about 30% [5][6][7] and increases with increasing life expectancy. The most common complication of herpes zoster, and one of the most challenging to treat, is post herpetic neuralgia, a painful condition often defined as pain persisting for more than 90 days after rash onset.8 According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
196
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(226 citation statements)
references
References 37 publications
(39 reference statements)
18
196
2
2
Order By: Relevance
“…A specific tool, the Zoster Brief Pain Inventory (ZBPI) has been developed to measure the impact of HZ/PHN-related pain and discomfort on seven general activities: work, sleep, walking, life enjoyment, mood, relations with others and general activity [20,27,28]. The results in the placebo group of a zoster vaccine clinical trial showed that the impact on ADL increased with age, and the impact continues after resolution of pain [20,29] (Fig. 2).…”
Section: Vaccine-preventable Infectious Diseases That Contribute To Cmentioning
confidence: 99%
“…A specific tool, the Zoster Brief Pain Inventory (ZBPI) has been developed to measure the impact of HZ/PHN-related pain and discomfort on seven general activities: work, sleep, walking, life enjoyment, mood, relations with others and general activity [20,27,28]. The results in the placebo group of a zoster vaccine clinical trial showed that the impact on ADL increased with age, and the impact continues after resolution of pain [20,29] (Fig. 2).…”
Section: Vaccine-preventable Infectious Diseases That Contribute To Cmentioning
confidence: 99%
“…Varicella-zoster virus (VZV) is a ubiquitous human-specific alphaherpesvirus that causes chickenpox (varicella) and establishes latency in cranial nerve and dorsal root ganglia during primary infection; many years later, this virus may reactivate to produce shingles (herpes zoster) and postherpetic neuralgia (PHN), which is a painful, refractory disease seriously affecting patient's quality of life (Gilden et al, 2000;Cohen et al, 2007;Drolet et al, 2010;Johnson et al, 2010;Weinke et al, 2010;Lukas et al, 2012). In the course of infection, VZV induces pathological abnormalities mainly in skin and nerves.…”
Section: Introductionmentioning
confidence: 99%
“…1 The lifetime risk to encounter HZ has been estimated at 20-30% 3 and the probability to develop HZ as well as the severity of pain increase with age. 4,5 Besides age, other riskfactors to HZ are a compromised or suppressed immune system and the female gender. 6,7 Although the rash heals within a month, 8 complications might occur.…”
Section: Introductionmentioning
confidence: 99%
“…9 It has been estimated that approximately 8-33% of HZ patients develop PHN, and the risk increases with age. 4,[10][11][12] Pain due to PHN may remain for months or even years 13,14 and available therapeutic options are only partially effective. 15 PHN has been shown to have a substantial impact on the patient's quality of life and functional status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation